2022
DOI: 10.21037/jtd-22-1363
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of plasma D-dimer levels in advanced non-small cell lung cancer patients treated with immune checkpoint inhibitors: a retrospective study

Abstract: Background: Plasma D-dimer is of great significance for the clinical exclusion of tumor-related thrombosis. Previous studies have shown its predictive role in non-small cell lung cancer (NSCLC) treated with chemotherapy. However, whether pretreatment D-dimer could predict the efficacy and prognosis in NSCLC patients treated with immune checkpoint inhibitors (ICIs) remains unclear.Methods: Advanced NSCLC patients treated with ICIs at the Chinese PLA General Hospital between January 2015 and March 2019 were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…As with other studies [44][45][46][47], we did not observe the diferences in PFS and OS between patients with nonsquamous and squamous. Pathological staging was not a prognostic factor afecting the efcacy of immunotherapy.…”
Section: Discussionsupporting
confidence: 89%
“…As with other studies [44][45][46][47], we did not observe the diferences in PFS and OS between patients with nonsquamous and squamous. Pathological staging was not a prognostic factor afecting the efcacy of immunotherapy.…”
Section: Discussionsupporting
confidence: 89%
“…Through a meta-analysis of seven studies involving a total of 1488 LC patients and 328 control groups, Biruk et al 37 concluded that the DD value was significantly higher in LC patients (standardized mean difference) 3.10; 95% CI 2.08, 4.12; P < 0.000) when compared with the health control group. In addition, Li et al 36 found that patients with a high level of plasma DD have a worse overall survival prognosis (hazard ratio (HR) = 1.742; 95% CI 1.542, 1.969; P < 0.001; I 2 = 72.1%) compared with these patients who have a normal plasma DD; elevated plasma DD is also a risk factor of progression-free survival in LC (HR = 1.385; 95% CI 1.169, 1.641; P = 0.003; I 2 = 69.1%). Similar to our findings, Chen et al 38 showed that the level of DD was associated with tumor stage; the level of neuron-specific enolase; the presence of distant metastasis, hyponatremia, and the progression of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing clinical evidence shows that the coagulation system of patients with malignant tumors is remarkably abnormal, and the level of DD is significantly elevated. 36 The mechanism may be that tumor cells or tissues around necrosis trigger the release of tissue factors, and activate coagulation factors X and XI in the external coagulation system and fibrinolysis system, resulting in the local production of plasmin to directly degrade the extracellular matrix, giving tumor cells the ability of invasion and metastasis. In this process, the released inflammatory mediators damage the vascular endothelial cells, leading to a hypercoagulable state of blood, which makes tumor cells adhere to the vascular wall.…”
Section: Discussionmentioning
confidence: 99%
“…Diminished serum albumin concentrations, emblematic of inflammatory and nutritional derangements, correspond to the grim prognosis of numerous virulent neoplasms [22,40]. Conversely, the elevation in D-dimer levels, indicative of hypercoagulable and inflammatory states, is associated with suboptimal survival across a diverse array of malignancies [41][42][43][44]. The composite measure, ADR, encompasses both albumin and D-dimer concentrations, potentially capturing a more comprehensive representation of the concomitant inflammatory, nutritional, and hemostatic perturbations in oncologic patients.…”
Section: Discussionmentioning
confidence: 99%